2018
DOI: 10.1136/bmjgast-2018-000201
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in coeliac disease: a population-based cohort study from a single centre in Southern Derbyshire, UK

Abstract: ObjectiveWith the advent of screening tests, it was hypothesised that milder cases of coeliac disease coming to diagnosis might have reduced risk of mortality. An earlier publication did not support this view. We have re-examined this issue employing a larger number of patients followed for a further 8 years.DesignPatients with coeliac disease from Southern Derbyshire, UK, were followed prospectively from 1978 to 2014 and included those diagnosed by biopsy and serology. Causes of death were ascertained. Standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 32 publications
4
22
1
Order By: Relevance
“…Similar to most studies, 1 , 4 , 5 , 11 we have confirmed that the mortality risks in CD patients are greatest during the first few years after diagnosis. It is plausible that at the time of diagnosis, patients in our cohort (all of whom were diagnosed prior to 1984) were more symptomatic and presented with more severe forms of the disease, as has been hypothesised to be the case with patients diagnosed in the pre‐serological era 8 , 22 . This coincides with the recognition that diagnosis at this time was more difficult than what it has become with serology and endoscopic biopsy.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Similar to most studies, 1 , 4 , 5 , 11 we have confirmed that the mortality risks in CD patients are greatest during the first few years after diagnosis. It is plausible that at the time of diagnosis, patients in our cohort (all of whom were diagnosed prior to 1984) were more symptomatic and presented with more severe forms of the disease, as has been hypothesised to be the case with patients diagnosed in the pre‐serological era 8 , 22 . This coincides with the recognition that diagnosis at this time was more difficult than what it has become with serology and endoscopic biopsy.…”
Section: Discussionsupporting
confidence: 66%
“…Coeliac disease (CD) patients are reported to have a higher mortality risk than the general population, although the reported magnitude of this increase in risk varies widely 1–8 . There is consensus that these increased mortality risks are observed predominantly within a few years of diagnosis (1–4 years) 1 , 4–6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a study done on a UK population did not reveal an increased risk of cardiovascular death in celiac patients compared to the general population (standardized mortality ratio: 1.23; 95% CI 0.98-1.51). However, the standardized mortality ratio was greater during the post-diagnosis period (after 2 years) than during the peri-diagnosis period (within 2 years) in CD patients [61].…”
Section: Discussionmentioning
confidence: 84%
“…1 lymphoma and adenocarcinoma. [5][6][7][8] Good adherence to a GFD can prevent the development of at least some of these complications. 7 With increasing pressure on the availability of gastroenterology outpatient clinic capacity many hospitals have elected to discharge patients with well controlled coeliac disease back to their general practitioners (GPs).…”
Section: Introductionmentioning
confidence: 99%